دور المعيار المحاسبي الدولي رقم 7 في تقيم السيولة للمؤسسة - محمد ضياء الحق, قطوطة (جامعة الوادي - University of Eloued, 2023)
التحليل المالي من أهم المواضيع التي تناولتها الدراسات الاقتصادية وذلك للضرورة التي يمليها التسيير من تخطيط ورقابة وتقييم للأداء المالي، وبالأخص التحليل بوسطة جدول التدفقات النقدية الذي أصبحت المؤسسات ملزمة على إعداده يعتبر تحليل قائمة التدفقات النقدية باستعمال أسلوب النسب المالية من خلال المعلومات المحاسبية التي تحتويها القائمة المعدة ملائمة لحاجة المؤسسة حسب النظام المحاسبي المالي وما يتطلبه المعيار المحاسبي الدولي السابع من أجل الرجوع إليها لمعرفة كيفية تسيير موارد المؤسسة والتحقق من النقدية المتاحة، وبما أنها مبنية على الأساس النقدي فهي مؤشر على صدق الربحية وإمكانية توقع التدفقات المستقبلية. Financial analysis is one of the most important topics dealt with in economic studies due to the necessity dictated by the management of planning, control and evaluation of financial performance, especially the analysis through the cash flow table which institutions have become obligated to prepare. Analysis of the cash flow statement using the financial ratio method is considered through the accounting information contained in the prepared list. It is appropriate for the institution’s needs according to the financial accounting system and what is required by the Seventh International Accounting Standard in order to refer to it to know how to manage the institution’s resources and verify the available cash. Since it is built on the cash basis, it is an indicator of the sincerity of profitability and the possibility of predicting future flows.
Keywords: المعيار المحاسبي الدولي- السيولة - التدفقات النقدية; International Accounting Standard - Liquidity - Cash Flows